Textualism, Materialism, Immersion, Interpretation - Uniłowski, Krzysztof (Praktyka Teoretyczna, 2019)
Krzysztof Uniłowski passed away earlier this December. For the last twenty years, he has been crucial to Polish literary studies. Writing on a broad range of topics – from reviews of contemporary Polish novels to essays on the idea of modernity, from class-oriented analyses of sci-fi books and TV shows to comments on the politics and ethics of literary criticism – he developed an impressive and highly unique critical perspective, or indeed: a unique language of criticism, one that has managed and will undoubtedly still manage to inspire countless critics of all generations. Throughout his work, Uniłowski drew heavily on historical materialism, constantly balancing his instinctive focus on the political – and, specifically, on class – with his equally instinctive conviction as to the irreplaceability of literary form. While we might not have agreed on every single issue – as is always the case on the Left – we in “Praktyka Teoretyczna” are proud to have called him not just an inspiration, but a comrade. Uniłowski passed away while putting finishing touches to the essay we’re presenting below. Unfortunately, he never managed to send us the finished abstract/summary for this article, so it falls to us to try and summarise its main theses. Krzysztof Uniłowski passed away earlier this December. For the last twenty years, he has been crucial to Polish literary studies. Writing on a broad range of topics – from reviews of contemporary Polish novels to essays on the idea of modernity, from class-oriented analyses of sci-fi books and TV shows to comments on the politics and ethics of literary criticism – he developed an impressive and highly unique critical perspective, or indeed: a unique language of criticism, one that has managed and will undoubtedly still manage to inspire countless critics of all generations. Throughout his work, Uniłowski drew heavily on historical materialism, constantly balancing his instinctive focus on the political – and, specifically, on class – with his equally instinctive conviction as to the irreplaceability of literary form. While we might not have agreed on every single issue – as is always the case on the Left – we in “Praktyka Teoretyczna” are proud to have called him not just an inspiration, but a comrade. Uniłowski passed away while putting finishing touches to the essay we’re presenting below. Unfortunately, he never managed to send us the finished abstract/summary for this article, so it falls to us to try and summarise its main theses.Krzysztof Uniłowski passed away earlier this December. For the last twenty years, he has been crucial to Polish literary studies. Writing on a broad range of topics – from reviews of contemporary Polish novels to essays on the idea of modernity, from class-oriented analyses of sci-fi books and TV shows to comments on the politics and ethics of literary criticism – he developed an impressive and highly unique critical perspective, or indeed: a unique language of criticism, one that has managed and will undoubtedly still manage to inspire countless critics of all generations. Throughout his work, Uniłowski drew heavily on historical materialism, constantly balancing his instinctive focus on the political – and, specifically, on class – with his equally instinctive conviction as to the irreplaceability of literary form. While we might not have agreed on every single issue – as is always the case on the Left – we in “Praktyka Teoretyczna” are proud to have called him not just an inspiration, but a comrade. Uniłowski passed away while putting finishing touches to the essay we’re presenting below. Unfortunately, he never managed to send us the finished abstract/summary for this article, so it falls to us to try and summarise its main theses. The issues raised in this erudite and formally complex piece include such fundamental questions as: in what sense do the fictional worlds resemble the non-fictional one, and how do we inhabit them? What’s the relationship between immersion and interpretation? What real-life figures can help us imagine or visualise our intimate yet inherently social relationship with the fictional (are we guests, dwellers, passersby...)? Uniłowski looks for answers in contemporary Marxist criticism (Eagleton, Jameson, Berardi), sci-fi and fantasy writing (Lem, Sapkowski, Martin), as well as modern continental philoso phy (Gadamer, Heidegger) and – in the last part of the essay – contemporary game studies. We’re happy to be able to present Uniłowski’s piece in two versions, the original Polish as well as its English translation (by Jakob Ziguras). In order to preserve the unmistakable flow of Uniłowski’s thought in English, small changes were introduced – with the author’s full approval – in the English version. We trust that our Polish-speaking readers will fin the comparison of the two versions interesting and instruc tive, as they seem to give a unique insight into Uniłowski’s writing process.